2016
DOI: 10.3233/cbm-160620
|View full text |Cite
|
Sign up to set email alerts
|

Use of the cell cycle progression (CCP) score for predicting systemic disease and response to radiation of biochemical recurrence

Abstract: Abstract. BACKGROUND: Determining the optimal treatment for biochemical recurrence (BCR) after radical prostatectomy (RP) is challenging. OBJECTIVE: We evaluated the ability of CCP score (a prognostic RNA expression signature) to discriminate between systemic disease and local recurrence in patients with BCR after RP. METHODS: Sixty patients with BCR after RP were selected for analysis based on: 1) metastatic disease, 2) non-response to salvage external beam radiotherapy (EBRT), and 3) durable response to salv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…Previous studies performed in more diverse patient populations have demonstrated a similar association of CCP score with various long‐term outcomes, including metastatic disease and PCa death . For example, in a heterogeneous cohort of patients with low‐ (32%) to intermediate‐/high‐risk (68%) PCa, Bishoff et al demonstrated a nearly 50% increase in the risk of BCR after RP (HR 1.47, 95% CI 1.23–1.76; P < 0.001) and a more than fourfold increase in the risk of metastatic disease (HR 4.19, 95% CI 2.08–8.45; P < 0.001) with a one‐point increase in biopsy‐derived CCP score.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Previous studies performed in more diverse patient populations have demonstrated a similar association of CCP score with various long‐term outcomes, including metastatic disease and PCa death . For example, in a heterogeneous cohort of patients with low‐ (32%) to intermediate‐/high‐risk (68%) PCa, Bishoff et al demonstrated a nearly 50% increase in the risk of BCR after RP (HR 1.47, 95% CI 1.23–1.76; P < 0.001) and a more than fourfold increase in the risk of metastatic disease (HR 4.19, 95% CI 2.08–8.45; P < 0.001) with a one‐point increase in biopsy‐derived CCP score.…”
Section: Discussionmentioning
confidence: 75%
“…In the present study, over one‐third of low‐risk patients had CCP scores >0, putting them at an appreciable risk of BCR after RP. Based on previous studies, these men likely harbour tumours with more aggressive underlying biology, and as such may not be as well suited for conservative management as their clinical and pathological features suggest . Nevertheless, it is important for healthcare providers to remember that the results of genetic tests, such as the CCP score, must be used in conjunction with other clinical information and patient demographics in order to create a stronger understanding of the overall clinical picture and underlying disease aggressiveness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study also evaluated RP specimens in a smaller cohort and found increased CCP score was associated with increased risk of systemic disease in those with BCR after RP, which may help identify those most likely to benefit from earlier salvage therapy. [61]…”
Section: Currently Available Testsmentioning
confidence: 99%
“…When CCP gene expression was added to other clinicopathologic features, the combined model was a significantly better predictor of recurrence than clinicopathologic features alone 9 . This observation has subsequently been validated in many independent cohorts, 10–14 including in patients following radical prostatectomy 15,16 . In fact, Cooperberg et al 15 validated a predefined model (clinical cell‐cycle risk [CCR] score) that combines the CCP score and the postsurgical Cancer of the Prostate Cancer Risk Assessment (CAPRA‐S) for determining patient prognosis post‐prostatectomy 15 .…”
Section: Introductionmentioning
confidence: 97%